Tufted astrocyte‐like glia in two autopsy cases of multiple system atrophy: Is it a concomitant neurodegenerative disorder with multiple system atrophy and progressive supranuclear palsy?. Issue 1 (21st December 2021) - Homma, Taku; Mochizuki, Yoko; Tobisawa, Shinsuke; Komori, Takashi; Takahashi, Kazushi
Abstract : Tufted astrocytes are one of the core histopathological features of progressive supranuclear palsy (PSP). To our knowledge, only three cases of multiple system atrophy (MSA) with PSP pathology have been reported. Here, we report two autopsy cases of MSA associated with the appearance of tufted astrocyte‐like glia (TuALG). Clinically, the patients' symptoms were atypical of MSA; one showed vertical gaze palsy, and the other was a long‐term survivor who progressed to a bedridden state shortly after the onset of the disease. These neuropathological observations were characterized by the copresence of MSA‐specific changes and TuALG in some of the cerebral cortices but few or none of the other PSP tau pathologies. These cases might emphasize the significance of TuALG in non‐PSP neurodegenerative disorders.